KONSTRUKSI GENDER DALAM NOVEL-NOVEL ANAK KARYA PENULIS ANAK - Else Liliani (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to describe identities, roles, and gender relations in children’s novels.The data sources were six children’s novels published by Dar! Mizan.The six novels werepurposively selected. The data were collected by repeatedly reading the novels, recorded,and classified based on the problem formulation categories. They were analyzed usingthe framework of feminist literary criticism, namely woman as a reader. The results ofthe study are as follows. First, gender equality has not been manifested because there isstill gender identity stereotyping. Characters with two identities, feminine and masculine,are described as weird characters. Second, there is inequality in the distribution of genderroles. Female characters have roles in public and domestic sectors and male charactersplay roles in the public sector only. Third, existing relations show varied but recognizablepatterns. The relations are manifested in different forms depending on contexts, sexes,ages, social classes, cultures, and descendant factors.